The Mortgage Portfolio of Mutual Savings Banks - Gregory, Paul M. (Quarterly Journal of Economics, 1947)
I. Introduction, 232. — II. Supply and allocation of investment funds: deposits, 233; the three main portfolios, 237; the volume of mortgage lending, 245; factors influencing the allocation of funds, 248. — III. Mortgage interest rates, 256. — IV. Comparison with yields on other investments, 261. — V. Summary and conclusions, 264.